Observations of glyoxal and methylglyoxal in a suburban area of the Yangtze River Delta, China - J.W. Liu; X. Li; Li, D. Q.; Xu, R. J.; Gao, Y. Q.; SY Chen; Y. Liu; Zhao, G.; Wang, H. C.; Wang, HL; Lou, S. R.; Chen, M. D.; et al. (Atmospheric Environment, 2020)
Glyoxal (GLY) and methylglyoxal (MGLY), as tracers of oxidation of volatile organic compounds (VOCs), play an important role in atmospheric chemistry. In this work, the concentrations of these two aldehydes were simultaneously measured online at a regional site in Jiangsu Province (China) during the 2018 EXPLORE-YRD campaign. The maximum measured concentration of GLY and MGLY was 0.47 and 6.68 ppb, respectively. As the campaign site was surrounded by farmland and the observations were recorded during harvest, significant enhancements to the concentration of GLY and MGLY were found owing to agricultural biomass burning. While the enhancement of MGLY relative to CO (0.0059 +/- 0.0012) was found to be consistent with previous study, the corresponding enhancement ratios of GLY were lower (0.0003 +/- 0.0001). The possibility of using the ratios between formaldehyde (HCHO), GLY, and MGLY concentrations as indicators of reactive VOC composition was investigated. Based on measured data and model simulation results, we found that the MGLY to HCHO ratio was sensitive to VOC precursors and reasonably well correlated with the reactivity of aromatics.
Keywords: Biomass burning; carbonyls; chemistry; emission factors; evolution; formaldehyde; glyoxal; hygroscopic growth; identification; methylglyoxal; particles; reactive trace gases; reactive voc composition; southern china